THE RELATIONSHIP BETWEEN CO2 EMISSIONS AND GROSS CAPITAL FORMATION IN TURKEY AND KUWAIT (The South East European Journal of Economics and Business, 2020)
The aim of this paper is to explore the potential link between gross capital formation and CO2 emissions by using the Toda and Yamamoto approach. The annual time-series data were collected for the period 1971- 2014. Due to the fact that Kuwait aims to become a major trading hub by 2035, it has made significant efforts to improve the infrastructure. Moreover, Turkey is also making strong efforts to improve the manufacturing sector as well as infrastructure, and represents an important trading hub that links Europe with the Middle East. Thus, Turkey and Kuwait are expected to strengthen their economic ties and expand trade, which was the motivation for comparing the link of interest in these two countries. The study’s findings confirm the bidirectional links between all of the variables of interest not only in the case of Turkey but also in the case of Kuwait, suggesting some important policy implications.